Violação à legítima: a tutela jurídica do direito dos herdeiros necessários sobre a parte indisponível da herança - Sette, Rafael Bortoletto (2024)
This dissertation intends to deepen the study of the mechanisms aimed at protecting the institution of forced heirship, in Brazilian Succession Law. By incorporating elements of Roman and Germanic law, the current Brazilian legislation establishes, as a cogent rule, the reservation of half of the inheritance in favor of the forced heirs (currently: descendants, ascendants and spouse). To correct possible embezzlements of such fraction, the Brazilian Civil Code establishes the remedies of reduction of liberalities and collation. However, these remedies are not capable, by themselves, of protecting the forced heirs’ rights, as the multiplicity of cases involving defraud of forced heirship has shown. For such purpose, null legal transactions are commonly concluded, usually based on illicit reason, fraud against mandatory law or simulation. Such invalid transactions are evident in various types of contracts (in particular purchase and sale, loans and indirect donations), as well as in corporate law mechanisms (constitution of a holding company aimed at hiding assets and harming the forced heirs’ rights) and, also, through private pension plans (VGBL). With greater sophistication, some use entities abroad (offshore companies, trusts or private foundations) to defraud the forced heirship. Nowadays, the possibility of defrauding through crypto assets is also envisaged. Any attempt to defraud the forced heirship may be rebutted by appropriate remedies, especially by filing a claim of nullity, based on any of the nullities abovementioned. Other remedies are the action to reduce a liberality (applicable when the author of the inheritance disposes of more than they could, failing to leave enough assets to guarantee the forced heirs’ rights), the suit of evasion (applicable when the obligation to collate is disrespected) and the disregard of the legal personality (applicable when defrauding the forced heirship is carried out between companies). The large number of judicial decisions involving this type of claim, on one hand, reveals that Brazilian courts, as a rule, respond appropriately to the attempts to defraud the forced heirship, and, on the other hand, invites us to reflect on the current legal status of forced heirship